INTERJEKSI DALAM ANIME ReLIFE - Mirha Yulinda; Hana Nimashita; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study examines the interjection in the ReLIFE anime. Words or expressions which are inserted into a sentence to convey suprise, strong emotion or to gain attention is called interjection. The purpose of this research is to describe the function and context of using interjection in the ReLIFE anime. This thesis examines function of interjection and the use of interjection based on Iwabuchi Tadasu’s theory and speech components by Hymes. The data of this research consist of 16 conversations which were taken from ReLIFE’s anime. They were analyzed with qualitative descriptive method to describing the data. The result are (1) found 16 interjection were used to express happiness, suprise, confusion, disbelief and upset, to call, to ask attention, to starting a conversation, to express approval, disapproval, rejection and denial (2) Interjections are used in informal situation and used by the speaker who have close relationship with the listener .Keywords: interjection, function, speech components, pragmatics.